The impact of teacher and learner positioning in the writing classroom - Mather, Nazarana (Journal for Language Teaching, 2022)
Existing research shows that in South Africa, there are reasons for concern regarding the achievements of a large proportion of Grade 6 learners in language learning. The impact of this poor language achievement affects their success rates across learning areas and in higher grades. It has also been found that historically, Grade 6 boys have achieved and continue to achieve lower results than their female peers in national and international language assessments. However, boys’ language learning in the Intermediate Phase in South African schools is surprisingly under-researched, particularly their writing skills development. This study uses positioning theory to understand Grade 6 boys’ writing development. A cycle of the Grade 6 writing programme, as prescribed by the Curriculum and Assessment Policy Statement (CAPS) (DBE, 2011), was observed and analysed. Although the teachers followed the same policy statement (the CAPS), it was found that their scaffolding approaches within the stages of the writing cycle differed significantly. It was concluded that there are significant links among three key elements: teacher knowledge, teachers’ and learners’ positioning in the writing process, and learners achieving the object of cognition in the stages of the writing cycle.